Immediate effects of alcohol marketing communications and media portrayals on consumption and cognition: a systematic review and meta-analysis of experimental studies - Kaidy Stautz; Kyle G. Brown; Sarah E. King; Ian Shemilt; Theresa M. Marteau (BMC, 2016)
Abstract Background Restricting marketing of alcoholic products is purported to be a cost-effective intervention to reduce alcohol consumption. The strength of evidence supporting this claim is contested. This systematic review aimed to assess immediate effects of exposure to alcohol marketing on alcoholic beverage consumption and related cognitions. Methods Electronic searches of nine databases, supplemented with reference list searches and forward citation tracking, were used to identify randomised, experimental studies assessing immediate effects of exposure to alcohol marketing communications on objective alcohol consumption (primary outcome), explicit or implicit alcohol-related cognitions, or selection without purchasing (secondary outcomes). Study limitations were assessed using the Cochrane Risk of Bias tool. Random and fixed effects meta-analyses were conducted to estimate effect sizes. Results Twenty four studies met the eligibility criteria. A meta-analysis integrating seven studies (758 participants, all students) found that viewing alcohol advertisements increased immediate alcohol consumption relative to viewing non-alcohol advertisements (SMD = 0.20, 95 % CI = 0.05, 0.34). A meta-analysis integrating six studies (631 participants, all students) did not find that viewing alcohol portrayals in television programmes or films increased consumption (SMD = 0.16, 95 % CI = −0.05, 0.37). Meta-analyses of secondary outcome data found that exposure to alcohol portrayals increased explicit alcohol-related cognitions, but did not find that exposure to alcohol advertisements influenced explicit or implicit alcohol-related cognitions. Confidence in results is diminished by underpowered analyses and unclear risk of bias. Conclusions Viewing alcohol advertisements (but not alcohol portrayals) may increase immediate alcohol consumption by small amounts, equivalent to between 0.39 and 2.67 alcohol units for males and between 0.25 and 1.69 units for females. The generalizability of this finding beyond students and to other marketing channels remains to be established.